Peranan Industri dalam Pertumbuhan Ekonomi Indonesia : Tantangan dan Peluang di Era Globalisasi - Baisyura, Alma (Maliki Interdisciplinary Journal, 2025)
Globalization has had a significant impact on the economic growth of developing countries, including Indonesia. Industry has a key role in spurring economic growth and creating jobs. This article discusses the role of the industrial sector in Indonesia’s economic growth as well as the challenges and opportunities faced in the era of globalization. With global competition, Indonesian industry must increase competitiveness through innovation, efficiency and sustainability. In addition, government policies that support the industrial sector are a crucial factor in achieving sustainable economic growth. In order to continue contributing to economic growth, Indonesia needs to optimize existing opportunities while strategically facing these challenges. The development of environmentally friendly green industries must be a priority in responding to global demands for sustainability and opening up new economic opportunities.